Partisipasi Petani Dalam Pengelolaan Sampah Plastik Melalui Bank Sampah di Kota Padang - Alfitri Alfitri (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2023)
One of the current environmental problems is plastic waste. One of the efforts to manage plastic waste in the community is through waste bank activities. This paper tries to explain the participation of farmers in the Pancadaya waste bank community in the suburbs area of Padang City, from a Giddens perspective. The research was conducted qualitatively by observation and interviews with several informants who were obtained purposively. The results of the research show that from the external dimension, several things are constraining and enabling the practice of participation by farmers, such as the distance factor and the existence of incentives.Meanwhile, from the internal dimension of farmers as subjects, participation as a social practice is largely due to unconscious motivation and practical consciousness. Only a small number of them participate in plastic waste management in waste banks based on discursive consciousness. Collaboration between waste banks and farmers as one element of customers and other parties is needed so that their participation practices are more driven by discursive consciousness